THE IMPACT OF STAGE AND THE EXTENT OF SURGERY ON LONG-TERM OUTCOMES IN OVARIAN CANCER PATENTS: THE IMPACT OF STAGE AND THE EXTENT OF SURGERY ON LONG-TERM OUTCOMES IN OVARIAN CANCER PATENTS - Radenkovic, Sandra (Medical Research, 2025)
Abstract Introduction: Standard therapy for patients with ovarian cancer involves cytoreductive surgery followed by platinum-based chemotherapy. Factors such as the stage of the disease at diagnosis, the histological type of the tumor, the size of the tumor and the presence of residual disease after cytoreductive surgery influence the prognosis of patients. Materials and methods: This scientific paper presents a retrospective study in which the following parameters were analyzed by analyzing data obtained from the documentation of patients treated for ovarian cancer at the Institute of Oncology and Radiology of Serbia and the Institute of Oncology of Vojvodina: age of patients, period from last chemotherapy to disease progression, number of bevacizumab cycles received, disease stage, reasons for discontinuation of bevacizumab, type of surgery and pathological verification of the disease. Results: We have shown that PFS is longer in the operated group (suboptimal operation) compared to those who were not operated (p < 0.05, Log-Rank and Breslow tests). There is no statistically significant difference in PFS between stages IIIc and IV, as determined by Log-Rank and Breslov tests. Also, in our research, there was no significant difference in the number of operated patients based on disease stage IIIc or IV (p = 0.36). Conclusions: Our data show that cytoreduction appears to confer a survival advantage in women with ovarian cancer treated with a combination of bevacizumab and chemotherapy. New studies should show whether the stage of the disease plays a significant role in the survival of patients with ovarian cancer.
Keywords: ovarian cancer, progression free survival, type of surgery, disease stage